Maternal Serum Vitamin B12 during Pregnancy and Offspring Autism Spectrum Disorder - Sourander Andre; Silwal Sanju; Surcel Heljä-Marja; Hinkka-Yli-Salomäki Susanna; Upadhyaya Subina; McKeague Ian W; Cheslack-Postava Keely; Brown Alan S (MDPI, 2025)
This study examined the association between maternal serum vitamin B12 levels during early pregnancy and offspring autism spectrum disorders (ASD) and subtypes. Based on a Finnish national birth cohort, case offspring (n = 1558) born in 1987-2007 and diagnosed with ASD by 2015 were matched with one control on date of birth, sex and place of birth. Maternal vitamin B12 levels were measured during first and early second trimesters of pregnancy. High maternal vitamin B12 levels (>= 81th percentile) was associated with increased risk for offspring childhood autism, adjusted odds ratio, 1.59, 95% confidence interval 1.06-2.41 (p = 0.026). No significant associations were observed between maternal vitamin B12 levels and offspring Asperger's or pervasive developmental disorder/NOS.